Paradoks Digitalisasi: Menakar Ketahanan Sektor UMKM Indonesia dalam Menghadapi Ancaman Resesi Global - Subandi Subandi; Putri Maharani (Lembaga Publikasi Ilmiah Nusantara, 2026)
The digital phenomenon paradox shows that despite the rapid increase in technology adoption, many Micro, Small, and Medium Enterprises (MSMEs) in Indonesia still face difficulties converting digital tools into resilient economic endurance, especially when confronting the threat of a global recession. This community service activity aims to strengthen the MSME ecosystem through strategic mentoring focused on digital financial literacy and data-driven supply chain optimization. The method used is Participatory Action Research (PAR) through a series of intensive workshops, risk management training, and the provision of a networking platform between business actors. The results of the activity indicate a significant increase in participants' capacity to manage digital cash flow and expand international market share to mitigate declining domestic purchasing power. In addition, this activity successfully mapped structural barriers such as technology infrastructure costs and technical skill gaps, which are often major hindrances. In conclusion, MSME resilience to global economic shocks relies not only on the possession of digital devices but on the ability to transform into adaptive and collaborative business models. The synergy between technological innovation and continuous mentoring is the main key to turning recession challenges into inclusive growth opportunities. Through this strengthening, MSMEs are expected to become the backbone of a more stable national economy and remain competitive on the global stage.